Penggunaan CSM Joomla dan Model RAD dalam Pembuatan Website Program Studi Sistem Informasi - stefanus setyo wibagso; Filipus Kurnia Angga (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
The study program is part of an organization in higher education that has activities to manage information related to all activities that occur within the scope of the organization. This information comes from various activities carried out by lecturers and students. The delivery of information related to activities that occur in the study program is not effective because it is still managed individually by the head of the study program. The study program website was created to support each contributor in managing and sharing information. Tools used to simplify the website development process was Joomla CMS because it had good features in content management. The method used was Rapid Application Development (RAD) as its development method. The results of using Joomla CMS-based website were very helpful for the head of the study program to view, monitor and evaluate activities that occur in his study program. Website development using Joomla CMS by applying the RAD method was also very effective in terms of time because the website creation process only took approximately 30 days.